2019
DOI: 10.1177/0143624419845117
|View full text |Cite
|
Sign up to set email alerts
|

A review on the application of photovoltaic thermal systems for building façades

Abstract: The hybrid photovoltaic-thermal system has shown great progress. Electrical energy is produced from PV panels while thermal energy is produced via a working fluid carried through the panels. In this paper, the vertical PV/T is introduced using working fluids such as air and liquid, which serve to control the excess temperature of the PV panels as well as to collect heat to be made available as thermal energy. Installations of PV/T systems on building façades, as well as integration with other technologies such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 109 publications
0
14
0
Order By: Relevance
“…Moreover, the application of the Trombe wall in different buildings was studied by Hu et al [153]. Further, Saretta et al [154] and Riaz et al [155] reported on BIPV façades prior to 2019 for the energy renovation of heritage buildings.…”
Section: Bipv-based Air Cyclementioning
confidence: 99%
“…Moreover, the application of the Trombe wall in different buildings was studied by Hu et al [153]. Further, Saretta et al [154] and Riaz et al [155] reported on BIPV façades prior to 2019 for the energy renovation of heritage buildings.…”
Section: Bipv-based Air Cyclementioning
confidence: 99%
“…In these systems, the heat produced from the PV/T is fed into the heat pump evaporator. The process is outlined: (1) direct expansion of the refrigerant from liquid to vapour, taking place inside the hydraulic circuit of the PV panels, (2) vapour compression for heating purposes, (3) refrigerant is condensed for heat transfer to water, (4) expansion valve (or capillary tube) used to turn high-pressure refrigerant to low-pressure liquid for reinsertion into PV/T evaporator (Riaz et al, 2020). Although this system is more complex than a conventional liquid cooling system, it provides a greater heat transfer from the PV to the working fluid than the prementioned systems, allowing for greater thermal and electrical efficiencies.…”
Section: Heat Pumpmentioning
confidence: 99%
“…Since, the hybrid system utilizes same area for the production of electricity and heat energy, it increases the overall efficiency of the system in terms of energy generation from per unit area [5]. The solar PVT system can be used for crop drying and air heating, and it can also be integrated with building facade, known as the building integrated PVT system (BI/PVT) [6]. The theoretical calculation says that the overall energy conversion efficiency of a hybrid system could be 60-80% [7].…”
Section: Introductionmentioning
confidence: 99%